Potential of Marine Biomolecules: Advances in Extraction and Applications of Proteins, Polysaccharides, and Antioxidant Compounds - Gabriela Sousa; Suzana Ferreira-Dias; Carla Tecelão; Vítor D. Alves (Foods)
Oceans are increasingly viewed as a new frontier for economic development, contributing to the bridge between food industry, sea bioeconomy, and health. Nowadays, oceans are under attention as a strategy for creating opportunities and driving innovation, and their vital importance will become even more evident in the years to come. Therefore, it is crucial to study oceans under a holistic approach, taking the maximum value of their abundant resources in a sustainable way. As such, blue bioeconomy is the path forward, since it is a development strategy that meets the economic potential without compromising the environmental health. A special look needs to be taken at the underutilized resources and by-products, which hold unexploited value. For instance, green macroalgae are widespread marine macroalgae that lack industry applications, despite being rich in biopolymers (polysaccharides) and antioxidants. Moreover, fish by-products are also rich sources of biopolymers, mostly proteins. Thus, among other potential uses, raw materials could be explored to produce functional edible coatings under a blue bioeconomy approach. A detailed characterization of raw materials is the first step for the development of value-added products. These topics will be addressed in this review.